Integration of Bioglass Into PHBV-Constructed Tissue-Engineered Cartilages to Improve Chondrogenic Properties of Cartilage Progenitor Cells - Xue, Ke; Zhang, Shuqi; Ge, Jin; Wang, Qiang; Qi, Lin; Liu, Kai (Frontiers in Bioengineering and Biotechnology, 2022)
(1) Background: the PHBV scaffold have proven to be a promising three-dimensional biodegradable and bioactive scaffold for the growth and proliferation of cartilage progenitor cells，the addition of Bioglass into PHBV was reported to increase the properties of the bioactive materials. (2) Methods: in current study, the influence of the addition of Bioglass into PHBV 3D porous scaffolds on the characteristics of cartilage progenitor cells based tissue engineered cartilage in vivo were compared. Cartilage progenitor cells were seeded into three-dimensional macroporous PHBV scaffolds and PHBV /10% Bioglass. The cartilage progenitor cells - scaffold constructs underwent six weeks in vitro chondrogenic induction culture, and then transplanted in vivo for another six weeks to evaluate the difference between cartilage progenitor cells-PHBV construct and cartilage progenitor cells-PHBV/10% Bioglass construct in vivo. (3) Results: compared with pure PHBV scaffold, PHBV/10% Bioglass scaffold has the better hydrophilicity and higher percentage of adhered cells. The cartilage progenitor cells-PHBV/10%Bioglass construct produced much more cartilage-like tissue with higher cartilage-relative gene expression and cartilage matrix protein production and better biomechanical performance than cartilage progenitor cells-PHBV construct. (4) Conclusions: the addition of Bioglass into PHBV three-dimensional macroporous scaffolds improve the characteristics of cartilage progenitor cells based tissue engineered cartilage in vivo.